Torn : rescuing the Gospel from the gays-vs.-Christians debate - Lee, Justin, 1977- (New York : Jericho Books, 2012)
"A loving and biblically-based response to the controversy that pits the church against the LGBT community and that divides Christians from each other"--Provided by the publisher.
Battle of the century -- God boy -- The struggle -- The truth comes out -- Why are people gay? -- Justin in Exgayland -- That the man should be alone -- South Park Christians -- The poisoned yeast -- Faith assassins -- The other side -- Back to the Bible -- Whatever commandment there may be -- Lightning rod -- The way forward.
Includes bibliographical references (p. 255-258).
Keywords: Homosexuality -- Religious aspects -- Christianity; Church work with gay people; Gay people -- Religious life; Church work with gays; Gays -- Religious life; Homosexuality -- Religious aspects -- Christianity